«O Natur!» Hölderlins erste Liebe oder Was Ökologie bedeuten könnte (Studia theodisca, 2025)
The international research on Hölderlin has certainly not overlooked how much Hölderlin’s entire poetry and thinking revolves around nature. Therefore, his efforts, so diverse in themselves, to understand what ‘nature’ actually means to us, appear highly relevant in the face of the currently emerging ecological crisis. This article aims to present a specific interpretive framework using the model of permeable concentric circles in which the various phases of Hölderlin’s conceptions of nature do not cancel each other out, but remain valid and insightful simultaneously, rather than mutually exclusive.